2020
DOI: 10.3390/ma13092052
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substrate Grain Size on Structural and Corrosion Properties of Electrodeposited Nickel Layer Protected with Self-Assembled Film of Stearic Acid

Abstract: In the present study, the impact of copper substrate grain size on the structure of the succeeding electrodeposited nickel film and its consequent corrosion resistance in 3.5% NaCl medium were evaluated before and after functionalization with stearic acid. Nickel layers were electrodeposited on two different copper sheets with average grain size of 12 and 25 µm, followed by deposition of stearic acid film through self-assembly. X-ray diffraction analysis of the electrodeposited nickel films revealed that the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Other factors that influence the character of SAMs are the sort of metal and its surface roughness (characterized by root-mean-square roughness Rrms) [ 49 ]. Generally, a rougher surface allows adsorption of more active molecules, but the irregularity baulks the formation of a densely packed, compact layer.…”
Section: Self-assembled Nanolayersmentioning
confidence: 99%
“…Other factors that influence the character of SAMs are the sort of metal and its surface roughness (characterized by root-mean-square roughness Rrms) [ 49 ]. Generally, a rougher surface allows adsorption of more active molecules, but the irregularity baulks the formation of a densely packed, compact layer.…”
Section: Self-assembled Nanolayersmentioning
confidence: 99%
“…The effect of the grain size of copper serving as a substrate for nickel film electrodeposition revealed a more hydrophilic behavior of the nickel film deposited on bigger copper grains. This was traced back to an indirect influence of the substrate grain size as the deposited nickel films were more homogeneous on the smaller copper grains . Noorbakhsh Nezhad et al also mentioned adsorbed hydrocarbons as a source for wetting differences.…”
Section: Introductionmentioning
confidence: 99%
“…This was traced back to an indirect influence of the substrate grain size as the deposited nickel films were more homogeneous on the smaller copper grains . Noorbakhsh Nezhad et al also mentioned adsorbed hydrocarbons as a source for wetting differences. On copper thin films, Platzman et al found higher contact angles on annealed films with less defects and grain boundaries and therefore expected reduced surface energy.…”
Section: Introductionmentioning
confidence: 99%
“…Nickel, as an industrial metal, has extremely important applications in many engineering fields, such as airplanes, radars, and batteries, due to its excellent ductility, magnetism, and mechanical properties [1][2][3][4]. In addition, nickel itself is not easily corroded and is widely used as a protective layer on device surfaces [5,6]. Although nickel can be used as a protective metal, its corrosion protection is limited.…”
Section: Introductionmentioning
confidence: 99%